The duality of ideas and values between couples and their reflection on the educational role of the family - Wadani, Jaman Hassan (Journal of Educational and Psychological Sciences, 2020)
This study aimed to discuss the duality of ideas and the duality of values between couples. It aimed also to showcase the reflections of that duality on the educational role of the family. The researcher used the descriptive analytic approach and the study reached multiple results, in particular:The intellectual duality and the duality of values is created because of the cultural, social and religious contrast between the couple.The intellectual convergence and the convergence of values between the couple is one of the most important factors in family stability.Children are negatively influenced by the intellectual contrast and the contrast of values between the parents because they receive two opposite messages which negate the educational effect of both of them.The researcher has recommended a number of recommendations, the most important of which are: Care for the partner selection stage: because it is of the utmost importance in building a family, so the intellectual and value convergence should be in the priorities of the partner selection criteria.
Keywords: The intellectual convergence; the educational role of the family; matrimonial competence; values; family education